If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying 6x + 2 + x = 1 + 4x + 4 Reorder the terms: 2 + 6x + x = 1 + 4x + 4 Combine like terms: 6x + x = 7x 2 + 7x = 1 + 4x + 4 Reorder the terms: 2 + 7x = 1 + 4 + 4x Combine like terms: 1 + 4 = 5 2 + 7x = 5 + 4x Solving 2 + 7x = 5 + 4x Solving for variable 'x'. Move all terms containing x to the left, all other terms to the right. Add '-4x' to each side of the equation. 2 + 7x + -4x = 5 + 4x + -4x Combine like terms: 7x + -4x = 3x 2 + 3x = 5 + 4x + -4x Combine like terms: 4x + -4x = 0 2 + 3x = 5 + 0 2 + 3x = 5 Add '-2' to each side of the equation. 2 + -2 + 3x = 5 + -2 Combine like terms: 2 + -2 = 0 0 + 3x = 5 + -2 3x = 5 + -2 Combine like terms: 5 + -2 = 3 3x = 3 Divide each side by '3'. x = 1 Simplifying x = 1
| 4b+8=-16 | | 3x+2+5=30 | | 4x+9=50 | | 8x^2+23x-3=0 | | 3x*x+5x-7=0 | | x/3+2=7(x-2) | | x+x-6=8 | | 3(x-2)-(3-x)=5x+4 | | 2(x-2)=2-x | | x/6=-2 | | 2-(-8)= | | 3(x+6)-2=15 | | 9+9c=9 | | 5x-4=3x+3x+8 | | p+10+(p-19)+2*p=699 | | p+10+p+19-2p=699 | | 3x+8-2x=-24 | | 11x-6=3x+26 | | 4x^2-11x+5=-2x+3 | | 6x^2-7x-49=0 | | y=3x^2+12x+5 | | 350=s+s+20 | | x^2+x+18=-8+4 | | x^2-6x+18=10 | | 4(b-2)=2(5-h) | | (4x-1)2=11 | | -.166(x-18)+0.5(x+2)=x+12 | | y=x^2+18+95 | | 8x=4x+4 | | 3x+48=6x+6 | | x^2-9x+16=8 | | .01x-7=13 |